A long post-reproductive lifespan is a shared trait among genetically distinct killer whale populations - Nielsen, MLK; Ellis, S; Towers, JR; Doniol-Valcroze, T; Franks, DW; Cant, MA; Weiss, MN; Johnstone, RA; Balcomb, KC, III; Ellifrit, DK; Croft, DP (Ecology and Evolution, 2021)
This is the final version. Available on open access from Wiley via the DOI in this record Data availability: Data to replicate the analyses are available from the online repository: https://doi.org/10.5061/dryad.6t1g1jwxx. Requests for access to raw data can be directed to the authors, the Center for Whale Research (www.whaleresearch.com) or Fisheries and Oceans Canada (www.dfo-mpo.gc.ca) The extended female post-reproductive lifespan found in humans and some toothed whales remains an evolutionary puzzle. Theory predicts demographic patterns resulting in increased female relatedness with age (kinship dynamics) can select for a prolonged post reproductive lifespan due to the combined costs of inter-generational reproductive conflict and benefits of late-life helping. Here we test this prediction using >40 years of longitudinal demographic data from the sympatric yet genetically distinct killer whale ecotypes: resident and Bigg’s killer whales. The female relatedness with age is predicted to increase in both ecotypes, but with a less steep increase in Bigg’s due to their different social structure. Here, we show that there is a significant post-reproductive lifespan in both ecotypes with >30% of adult female years being lived as post-reproductive, supporting the general prediction that an increase in local relatedness with age predisposes the evolution of a post reproductive lifespan. Differences in the magnitude of kinship dynamics however, did not influence the timing or duration of the post-reproductive lifespan with females in both ecotypes terminating reproduction before their mid-40s followed by an expected post reproductive period of ~20 years. Our results highlight the important role of kinship dynamics in the evolution of a long post-reproductive lifespan in long-lived mammals, while further implying that the timing of menopause may be a robust trait that is persistent despite substantial variation in demographic patterns among populations. Nuffield Foundation Natural Environment Research ...